2005
DOI: 10.1093/tropej/fmi049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of WHO Classification of Hypothermia in Sick Extramural Neonates as Predictor of Fatality

Abstract: The objective of this study is to correlate the severity of hypothermia in sick extramural neonates with fatality and physiological derangements. This is a prospective observational study carried out at the referral neonatal unit of a teaching hospital admitting extramural neonates. The subjects comprised of 100 extramural hypothermic neonates transported to the Referral neonatal unit. Neonates weighing more than 1000 g, with abdominal skin temperature less than 36.5 degrees C at admission were included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 12 publications
2
34
1
1
Order By: Relevance
“…[1][2][3] Our study revealed higher odds of IVH with moderate hypothermia and higher odds of death with both severe and moderate hypothermia. Despite the association of ROP, oxygen use at 36-week-corrected age and late sepsis with hypothermia on bivariate analyses, in risk adjusted logistic regression models, hypothermia was not a significant risk factor, likely representing the confounding effect of factors such as birth weight.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…[1][2][3] Our study revealed higher odds of IVH with moderate hypothermia and higher odds of death with both severe and moderate hypothermia. Despite the association of ROP, oxygen use at 36-week-corrected age and late sepsis with hypothermia on bivariate analyses, in risk adjusted logistic regression models, hypothermia was not a significant risk factor, likely representing the confounding effect of factors such as birth weight.…”
Section: Discussionmentioning
confidence: 48%
“…[1][2][3][4][5] The World Health Organization (WHO) established criteria for assessing hypothermia and published a guidebook on the thermal protection of newborns in 1997, indicating that this issue is a worldwide problem even for term infants, particularly in developing nations. 6 WHO classifications of hypothermia are (1) cold stress or mild hypothermia: 36.0 to 36.4 1C (96.8 to 97.51 F); (2) moderate hypothermia: 32.0 to 35.9 1C (89.6 to 96.61 F); and (3) severe hypothermia: below 32 1C (<89.61 F).…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated a dramatic effect of comorbidities and confirmed that hypothermia has a much worse outcome when associated with other newborn problems. Fatality rates increased to 71.4% with hypoglycemia, 83.3% with hypoxia, and 90.9% with shock [61].…”
Section: Associations Of Hypothermia With Newborn Morbidity and Mortamentioning
confidence: 94%
“…Moreover, hypothermia increases oxygen consumption, thus leading to hypoxia and subsequently pulmonary vasoconstriction which, in turn, declines surfactant production and worsens respiratory distress. The presence of comorbidities with hypothermia increases the fatality rate, so adding a higher category to the severity of hypothermia would represent an effective addition to the WHO classification of the severity of hypothermia [8].Large surface area of neonates in relation to their small body weight makes them more vulnerable to hypothermia than fullterm babies. Preterm neonates have a higher transepidermal water loss than term due to their immature epidermal layer [9].…”
mentioning
confidence: 99%
“…Since the head constitutes a major portion of the body surface area in neonates and the brain plays the role of a prime heat-generating organ, head covering has been an effective technique in preventing temperature reduction in neonates [14]. But all these techniques are still insufficient in very preterm neonates.Ambient temperature of delivery room: According to WHO's recommendation the temperature of delivery rooms' should be adjusted at no less than 25°C, while the International Liaison Committee on Resuscitation (ILCOR) 2010 recommends that it should be ≥ 26 °C [3][4][5][6][7][8][9][10][11][12][13][14][15]. However, these suggestions aren't feasible targets.…”
mentioning
confidence: 99%